The optimal effect-site concentration of propofol for endotracheal suctioning in intensive care unit patients - Hou-Chuan Lai; Meei-Shyuan Lee; Shinn-Long Lin; Lok-Hi Chow; Bo-Feng Lin; Zhi-Fu Wu (Journal of Medical Sciences, 2017)
Objective: To evaluate the optimal effect-site concentration (Ce) of propofol during endotracheal suction (ETS) in the postoperative Intensive Care Unit (ICU) sedated patients. Design and Setting: The study design was a prospective randomized clinical study in a 13-bed ICU in a medical center. Patients: Thirteen mechanically ventilated patients were included in this study. Methods: All included postoperative patients received sedation by target-controlled infusion (TCI) of propofol under bispectral index (BIS) monitoring and 2–4 μg/kg/h fentanyl infusion for analgesia to keep numerical rating scale ≤4. While ETS was need, the sedation interventions were performed. We used the up-and-down method with a step size of propofol Ce 0.2 μg/ml for the next intervention. The sedation interventions of 1, 2, and 3 were baseline propofol Ce, baseline propofol Ce +0.2 mg/ml, and baseline propofol Ce +0.4 μg/ml, respectively. The predetermined propofol Ce was maintained for 5 min before ETS. Arterial systolic blood pressures (SBPs), arterial diastolic blood pressure (DBP), heart rates (HRs), and BIS before and after ETS were recorded. No moderate or severe coughing with limb movement was the primary outcome, and the surge of SBP, DBP, and HR ≤20% of baseline was the secondary outcome. Results: There were 39, 72, and 45 ETS were performed in the intervention 1, 2, and 3, respectively. In the primary outcome, the successful rates of ETS were 100%, 37.5%, and 15.4% in the intervention 3, 2, and 1, respectively (P < 0.001). In the secondary outcomes, the successful rates were 100% in all interventions. However, the surge of SBP (P = 0.009), DBP (P = 0.025), and HR (P = 0.009) were significant higher in the intervention 1 and 2 than the intervention 3. Right after the ETS, significant increase in BIS level was observed in the intervention 1 (13.9± 7.9) and 2 (14.4± 7.5) except for intervention 3 (−2.8± 14.5) (P = 0.003). Conclusions: An increase of propofol Ce 0.4 mg/ml for 5 min before ETS provided adequate sedation result in markedly attenuated ETS-induced coughing, limb movement, and hyperdynamic status during ETS while the use of TCI propofol sedation in postoperative ICU patients.